DESIGN OPTIMIZATION OF COATING CHARACTERISTICS IN A TANGENTIAL FLUIDIZED BED COATER USING TAGUCHI METHOD - HASSAN, LUQMAN HAKIM (2014)
This work is designed to investigate the influence of numerous process parameters affecting the coating characteristics in a tangential fluidized bed through a series of experiments. The solution composing urea, starch, borate and lignin were here used as coating material. It was accordingly followed by studying the impact from the process parameters - inlet air temperature, disc rotation speed and spraying rate. The analyzed coating characteristics included mass coating variability, hardness strength and coating thickness and for optimization ofprocess parameters, Taguchi Method was used as the design of experiment. Further, to evaluate the coating characteristics, a series of nine experiments were executed based on L9orthogonal array and SN ratio here was used as response index. The results then showed that the optimum process parameters to produce the lowest mass coating variability were found in inlet air temperature at 80°C, disc rotation speed at 6.28 rad/s and spraying rate at 7.33x10"8 m3/s.